Karakterisasi Sifat Listrik dan Magnetik PANI/HCl/Fe3O4 akibat Penambahan Fe3O4 pada Komposit PANI/HCl - Purwanto, Purwanto; Kusumawati, Diah Hari (Sains & Matematika, 2013)
Fabrication PANi/HCl has been carried out by interfacial polymerization method, Fe3O4 nanoparticles by coprecipitation method and composite with compacting method. In the manufacture of composites, the addition of Fe3O4 nanoparticles aims to improve the electrical properties and characteristics of the magnetic properties of the composite PANi/HCl/Fe3O4. Characterization was conducted on the electrical conductivity measurements, characterization of XRD and VSM. Characterization results in this study could be seen that with the addition of Fe3O4 in PANi/HCl/Fe3O4 the electrical conductivity decreases significantly with increasing addition of Fe3O4. The maximum electrical conductivity of PANi/HCl at 16,667 S/cm decreased with the highest reduction at 40% Fe3O4 with a value of 21.1 Ã— 10-4 S/cm. With the addition of Fe3O4 nanoparticles of the magnetic properties PANi/HCl in PANi/HCl/Fe3O4 composites increased significantly with increasing addition of Fe3O4 nanoparticles. The enhancement magnetic properties was shown by the increasing value of saturation magnetization (Ms) PANi/HCl in the composite PANi/HCl/Fe3O4. For the PANi/HCl with a value of Ms = 25.48 Ã— 10-4 emu/cm3 experienced the highest increase in the addition of 40% Fe3O4, that is the value of Ms = 18.5 emu/cm3.